PENGARUH PELAKSANAAN GOOD CORPORATE GOVERNANCE TERHADAP MOTIVASI KERJA PADA UNIVERSITAS SUMATERA UTARA - Katharina, Ninta (Akuntansi Prima, 2020)
The purpose of this study was to determine the effect of the implementation of Good Corporate Governance proxied by transparency, accountability, responsibility, independence and fairness towards motivation at the University of North Sumatra. The population in this study were employees of the University of North Sumatra as many as 100 respondents. Researchers used the entire population to be a sample of research (census research) as many as 100 samples. In this study, researchers used simple linear regression and 2 stages of testing namely the classic assumption test using normality test, multicollinearity test and heterokedasticity test while in hypothesis testing using t test . The results of this test prove that Good Corporate Governance is proxied by accountability, independence does not have a significant effect on motivation while Good Governance is proxied by significant responsibility for motivation. In this study, researchers provide suggestions for further researchers, are expected to be more widespread or include and add research variables to all employees and lecturers who use the Good Governance system at the University of North Sumatra